Influence of legume diversification and fertilization on soil potassium pools under distinct cropping system ecologies: insight from 14-years study - Nath, Chaitanya Prasad; Dutta, Asik; Hazra, Kali Krishna; Kumar, Narendra; Praharaj, C. S.; Kumar, Mukesh; Hashim, Mohammad; Dixit, G. P. (Frontiers in Sustainable Food Systems, 2025)
Sustaining levels of soil potassium (K) pools in soils across agro-ecologies are crucial for optimizing nutrient use, prevent K depletion, and ensure long-term soil health. This study explores the underlying mechanisms and interconnections among various K pools under contrasting upland (maize-based) and lowland (rice-based) ecologies from a 14 years long-term field experiment conducted on Fluvisols encompassing four cropping systems (main plots) and three nutrient management strategies (sub-plots). The maize–wheat–maize–chickpea system recorded the highest water-soluble (15.6 kg ha−1) and exchangeable K (162.7 kg ha−1), while pigeonpea–wheat had the highest non-exchangeable K (1826.2 kg ha−1), over maize–wheat (p < 0.05). In the 0–15 cm, INM significantly improved soil K fractions over RDF, with water-soluble, exchangeable, non-exchangeable, and total K increasing by 37.6, 17.9, 12.2, and 10.1%, respectively. In lowland ecology, the rice–wheat system contains 50 and 30% higher water-soluble K than rice–wheat–rice–chickpea and rice–wheat–mungbean at 0–15 cm. While, exchangeable and non-exchangeable K increased by 3.4–13% in the same over other systems. At 15–30 cm, rice–wheat–rice–chickpea recorded 9–10% higher water-soluble K and exchangeable K than other systems. Ecology-wise, a notable finding was that lowland soils exhibited 3–4 times higher water-soluble K, 52% more exchangeable K, and 5–10% higher non-exchangeable K than upland soils (p < 0.05). Wheat yields correlated significantly with total, exchangeable, and water-soluble K in upland. Rice yields in lowland significantly correlated with total, non-exchangeable, and water-soluble K, indicating the importance of soil K reserves in crop productivity. Systems like pigeonpea–wheat, maize–wheat–maize–chickpea, and rice–wheat–rice–chickpea were most effective in replenishing K reserves, offering a scalable strategy to support soil K levels against intensive cereal based systems underlining the ecological benefits of legume inclusion and integrated nutrient management in sustaining soil K dynamics across diverse production systems.